Duration of Growth Spurt based on Cervical Vertebrae Maturation In Indonesia Population - Seno Pradopo; Sindy Cornelia Nelwan; Ardianti Maartrina Dewi; Amalia Wimarizky; Achmad Nadian Permana; Zurairahbt Ibrahim; Ainuddin Yushar Md Yusof (Institute of Medico-legal Publications Pvt Ltd, 2021)
Context: Human development consists of periods of accelerated growth where there is an acceleration ofgrowth followed by a period of slower growth. The timing of pubertal growth spurt and maximal growthrate during this developmental phase is different in boys and girls. The increase in growth rate in girlsusually occurs at the onset of puberty while boys experience a relatively slow increase in growth rate atpuberty.Aims:to compare the differences in the duration of growth spurtbetween girl andboy in Indonesianpopulations in terms of the Cervical Vertebrae Maturation (CVM) seen in the lateral cephalogram. Thisinformation is important to determine the right time and orthodontic treatment plan in order to get maximumtreatment results.Methods and Material: The research variables were divided into 3 types, namely dependent variables(chronological age), independent variables (Cervical Vertebrae Maturation stage, gender). Every sample thatmet the criteria was performed skeletal maturity analysis using Cervical Vertebrae Maturation (CVM) oneach cephalometric photo Skeletal analysis with Cervical Vertebrae Maturation (CVM) by looking at bonematurationResults: There were differences in the mean / mean age of skeletal maturity in terms of changes in CS 3to CS 4 between male and female samples (p <0.05). The male sample required a duration of age to reachmaturity, namely 15.879 months. Meanwhile, the female sample only required the duration of age to reachmaturity, namely 5,184 monthsConclusions:Girls in this study population had a faster growth spurt duration than boys. This is marked by achange in the age of skeletal maturity between the two, which is approximately 10 months apart.